Photodynamic Therapy Combined with Antihypoxic Signaling and CpG Adjuvant as an In Situ Tumor Vaccine Based on Metal–Organic Framework Nanoparticles to Boost Cancer Immunotherapy. Issue 1 (20th November 2019) - Cai, Zhixiong; Xin, Fuli; Wei, Zuwu; Wu, Ming; Lin, Xinyi; Du, Xiaofan; Chen, Geng; Zhang, Da; Zhang, Zhenxi; Liu, Xiaolong; Yao, Cuiping
Abstract: Photodynamic therapy (PDT) usually aggravates tumor hypoxia, which promotes the survival and metastasis of residue cancer cells; furthermore, although PDT‐induced immunogenic death of cancer cells can induce host antitumor responses, such responses are generally weak and not enough to eliminate the residue cancer cells. Here, metal–organic framework (MOF)‐based nanoparticles to combine PDT, antihypoxic signaling, and CpG adjuvant as an in situ tumor vaccine to boost host anticancer responses after PDT are designed. The MOF‐based nanoparticles are self‐assembled from H2 TCPP and zirconium ions with hypoxia inducible factor (HIF) signaling inhibitor (ACF) and immunologic adjuvant (CpG) loading, and hyaluronic acid (HA) coating on the surface. The final nanoparticles (PCN‐ACF‐CpG@HA) can specifically target cancer cells overexpressing CD44 receptor though HA; the aggravated hypoxic survival signaling after PDT can be blocked by ACF to inhibit the HIF‐1α induced survival and metastasis. With the help of CpG adjuvant, the tumor associated antigens generated from PDT‐based cancer cell destruction can initiate strong antitumor immune responses to eliminate residue cancer cells. Taken together, a novel in situ immunostimulatory strategy is designed to synergistically enhance therapeutic effects of PDT by activating host antitumor immune‐responses both in vitro and in vivo, which may have great potential for clinical translation in future. Abstract : Herein, PCN‐ACF‐CpG@HA nanoparticles are fabricated through self‐assembling of H2TCPP and zirconium ions, with hypoxia inducible factor signaling inhibitor (ACF) and immunologic adjuvant (CpG) loading as well as a hyaluronic acid coating on the surface, for integrating photodynamic therapy (PDT), antihypoxic signaling, and immunologic adjuvant as an in situ tumor vaccine to improve PDT efficiency and achieve long‐term therapeutic outcomes by boosting host antitumor immuno‐responses.